The Effect of Switching Ranibizumab to Aflibercept in Refractory Cases of Macular Edema Secondary to Ischemic Central Vein Occlusion - Lehmann-Clarke, L.; Dirani, A.; Mantel, I.; Ambresin, A. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: Macular edema resulting from central retinal vein occlusion is effectively treated with anti-vascular endothelial growth factor injections. However, some patients need monthly retreatment and still show frequent recurrences. The purpose of this study was to evaluate the visual and anatomic outcomes of refractory macular edema resulting from ischemic central retinal vein occlusion in patients switched from ranibizumab to aflibercept intravitreal injections.Patients and Methods: We describe a retrospective series of patients followed in the Medical Retina Unit of the Jules Gonin Eye Hospital for macular edema due to ischemic central retinal vein occlusion, refractory to monthly retreatment with ranibizumab, and changed to aflibercept. Refractory macular edema was defined as persistence of any fluid at each visit one month after last injection during at least 6 months. All patients had to have undergone pan-retinal laser scan.Results: Six patients were identified, one of whom had a very short-term follow-up (excluded from statistics). Mean age was 57 ± 12 years. The mean changes in visual acuity and central macular thickness from baseline to switch were + 20.6 ± 20.3 ETDRS letters and − 316.4 ± 276.6 µm, respectively. The additional changes from before to after the switch were + 9.2 ± 9.5 ETDRS letters and − 248.0 ± 248.7 µm, respectively. The injection intervals could often be lengthened after the switch.Conclusions: Intravitreal aflibercept seems to be a promising alternative treatment for macular edema refractory to ranibizumab in ischemic central retinal vein occlusion.
Keywords: Aflibercept; ischämischer Zentralvenenverschluss; Makulaödem; refraktär